Analisis Faktor-Faktor Yang Mempengaruhi Return Saham (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar diBursa Efek Indonesia Periode 2010-2014) - SYELIANA, SYELIANA; , Drs. Muhammad Abdul Aris, M.Si (2017)
Stock return is the result obtained from investment activities. The factors that affect stock returns must be known so that hope to obtain maximum returns can be achieved. This study aimed to analyze the influence of Earning Per Share, Price Earning Ratio, Debt To Equity Ratio, Return on Equity on Stock Return. Population and sample in this research is a mining company listed on the Indonesia Stock Exchange 2010-2014. Sampling technique used is purposive sampling. Methods of data collection is done by using the documentation. The number of samples processed as many as 49 firm years. Research analysis techniques using multiple linear regression. The results showed that the Price Earning Ratio and Debt To Equity Ratio Return effect on Stocks Return, while Earning Per Share and Return On Equity no affect on Stock Return.